Infância e Drummond: uma leitura das obras infantis - Dantas, Rafaela Skarlaty Lócio (2016)
This research, of a bibliographic and documentary nature, has as its core a reconsideration on how it has been thought Drummond's child work within the specialized university community in an attempt to contribute to the studies that have been done on the literary production of this author. Therefore, it proposes a critical reading of five drummondian works made for the childhood: Elephant (1983), The color of each (1996a), The password of the world (1996b), Drummond Boy (2012) and History of Two Loves (1985). Among these, only the last book, published by Record, was intentionally written for the children, since the first was extracted from The rose of the people (1945) and editorially readdressed, while the others were organized in anthologies that were illustrated by the same publisher (except for Drummond Boy, which was published by Companhia das Letras). Considering such data, and based on the childhood thematic relevance throughout the Drummond's work, this research attempts to track childhood representations noticed by means of literary production and reading practices contained in the books referred above, either through the text itself, or by the reading protocols conformed by the editorial procedures. To this end, the research will be subsidized by the studies of: a) Peter Hunt, Regina Zilberman, Mônica Menezes and Vera Teixeira de Aguiar, about children's literature; b) Roger Chartier, on the conceptual notions of practice, representation, interpretation community, ownership and reading protocol; c) Philippe Ariès, Neil Postman e Jens Qvortrup about childhood social conception; d) and Antonio Carlos Secchin, Alcides Vilaça among other critics, concerning childhood in the literary production of Carlos Drummond de Andrade